Trends in changing the structure of anesthesia at the advanced stages of medical care in modern armed conflict - A. E. Tsygankov; M. E. Semenov; V. E. Petrov; E. А. Usoltsev; S. V. Sidelkin; E. N. Ershov (Вестник анестезиологии и реаниматологии)
The objective was to analyze the structure of anesthesia provided to the wounded at the advanced stages of medical care in the active phase of hostilities.Materials and methods. A retrospective analysis of the medical data of anesthesia was performed. The data on the structure of anesthesia in military medical organizations of 1–3 levels in the zone of a special military operation for the period from 01.2023 to 07.2024 were analyzed.Results. In the structure of combat trauma, with the need for surgical intervention, gunshot wounds amounted to 85.2%, there was a predominance of combined (71.5%) and multiple (19.8%) wounds.The low proportion of combined general anesthesia and the lack of use of inhalation anesthesia at some stages is explained by the special conditions of care. Regional anesthesia (RA), including as part of combined anesthesia, in the structure of anesthesia at the stages of emergency specialized surgical care amounted to 34.5%, and at the stages of qualified surgical care – 25.4%. The lowest rates of RA use were at the stages of level 1, as well as at the stages of level 2 with a 100% flow of primary wounded.Conclusion. RA occupies a significant share in the structure of anesthesia at the military stages of medical evacuation; an increase in the frequency of its use is possible due to the introduction of ultrasonic navigation.